2021
DOI: 10.24191/abrij.v7i1.14256
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Intention to Use Technology of Online Food Delivery Services Among Young Adults

Abstract: Online food delivery services have experienced tremendous growth in the food industry. Food delivery apps had gathered this opportunity adjusting to restaurant and food delivery services as an alternative to increasing income and for customers to remotely order their foods. This study aims to determine the relationship between information quality, performance expectancy, effort expectancy and social influence with continuous use intention of food delivery apps from Malaysian young adults’ context. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The closer the value to 1, the greater internal consistency of the element in the scale. The alpha coefficient is 0.847 bring the meaning that the element of the instrument having the high internal consistency; with the reliability value of the items were above the suggested which is more than 0.70 Ariffin et al, 2021).…”
Section: Validity and Reliabilitymentioning
confidence: 88%
“…The closer the value to 1, the greater internal consistency of the element in the scale. The alpha coefficient is 0.847 bring the meaning that the element of the instrument having the high internal consistency; with the reliability value of the items were above the suggested which is more than 0.70 Ariffin et al, 2021).…”
Section: Validity and Reliabilitymentioning
confidence: 88%
“…Various food suppliers offer their services through FDAs in Malaysia, and some examples are Food Panda, Dahmakan, DeliverEat and GrabFood. These food delivery services are mainly concentrated in Kuala Lumpur, Klang Valley, Penang and Johor Bahru (Ariffin et al, 2021). It is reported that 81% of customers in Malaysia used Foodpanda as their FDA of choice in 2021, followed by GrabFood as their second choice at 70%.…”
Section: Food Delivery Applications (Fdas)mentioning
confidence: 99%
“…The very few studies that have examined this subject overlooked crucial linkages, resulting in fragmented or inconclusive outcomes and relationships among variables, thus limiting the understanding of the phenomenon. Previous research, for example, has explored the interconnections among information quality, service quality, and system quality continuance intention (Ariffin et al, 2021; Lee et al, 2017; Wang et al, 2021). Meanwhile, many studies have examined the effects of dimensions of food delivery apps' quality on overall service quality and continuance intention (Cho et al, 2019; Choi, 2020; Zhuang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%